Improving the Quality of Print Media Learning with Press Screening Tech-niques Through Teaching Books - Masnuna; Mahimma Romadhona (Future Science, 2020)
The purpose of this study is to compile a textbook for Visual Communication Design 2 in the Visual Communication Design study program. This course discusses the logo as a visual identity and its implementation in print media using the screen-printing press technique. The research method uses two stages, namely the creation stage and the publication stage. The creation stage includes pre-production, production, and post-production, while the publication stage includes registration of book publishing and book releases. The result of this research is a textbook entitled